Social control in the regulatory compliance of the INFOBRAS system in the entity provider of sanitation services Tacna S.A. - Calderón Paniagua, Dennys Geovanni (2021)
The objective of this research was the evaluation, through social control, of the regulatory compliance of the INFObras system at the Entidad Prestadora de Servicios de Saneamiento Tacna S.A. (EPS Tacna S.A.). The research was of a basic type, with a descriptive - explanatory level design, since it sought to generate knowledge  by evaluating the level of regulatory compliance with the registration of public works in the INFObras system in EPS Tacna S.A. during the period 2013 - 2020, strengthening the control and transparency of public works in order to favor social control by citizens. The population consisted of the 86 public works registered in the INFObras system and the 17 investment projects registered in the budget execution monitoring system of the Ministry of  Economy and Finance (MEF). It was concluded that the application of social control in the evaluation of information from the INFObras system of the Comptroller General of the Republic of Peru (CGR) and the budget execution system of the MEF revealed a high level of noncompliance in the registration of public works in the INFObras system by EPS Tacna S.A., limiting the right to citizen participation of the population of the Tacna region, that is, to have the possibility of knowing if the works in their region are being developed within the established timeframe, with the required quality and fulfilling their public purpose.